Stem‐cell therapy in ST‐segment elevation myocardial infarction with reduced ejection fraction: A multicenter, double‐blind randomized trial. Issue 3 (22nd March 2018) - Nicolau, José C.; Furtado, Remo H.M.; Silva, Suzana A.; Rochitte, Carlos E.; Rassi, Anis; Moraes, João B.M.C.; Quintella, Edgard; Costantini, Costantino R.; Korman, Adrian P.M.; Mattos, Marco A.; Castello, Hélio J.; Caixeta, Adriano; et al.
Abstract : Background: Left ventricular ejection fraction (LVEF) is a major determinant of long‐term prognosis after ST‐segment elevation myocardial infarction (STEMI). STEMI patients with reduced LVEF have a poor prognosis, despite successful reperfusion and the use of renin‐angiotensin‐aldosterone inhibitors. Hypothesis: Intracoronary infusion of bone marrow–derived mononuclear cells (BMMC) may improve LVEF in STEMI patients successfully reperfused. Methods: The main inclusion criteria for this double‐blind, randomized, multicenter study were patient age 30 to 80 years, LVEF ≤50%, successful angioplasty of infarct‐related artery, and regional dysfunction in the infarct‐related area analyzed before cell injection. Cardiac magnetic resonance imaging was used to assess LVEF, left ventricular volumes, and infarct size at 7 to 9 days and 6 months post–myocardial infarction. Results: One hundred and twenty‐one patients were included (66 patients in the BMMC group and 55 patients in the placebo group). The primary endpoint, mean LVEF, was similar between both groups at baseline (44.63% ± 10.74% vs 42.23% ± 10.33%; P  = 0.21) and at 6 months (44.74% ± 12.95 % vs 43.50 ± 12.43%; P  = 0.59). The groups were also similar regarding the difference between baseline and 6 months (0.11% ± 8.5% vs 1.27% ± 8.93%; P  = 0.46). Other parameters of left ventricular remodeling, such as systolic and diastolic volumes, as well as infarct size, were also similar between groups. Conclusions: In this randomized, multicenter, double‐blind trial, BMMC intracoronary infusion did not improve left ventricular remodeling or decrease infarct size.